Nitrooleic Acid Protects against Cisplatin Nephropathy: Role of COX-2/mPGES-1/PGE2 Cascade. (11th March 2015) - Wang, Haiping; Jia, Zhanjun; Sun, Jing; Xu, Liang; Zhao, Bing; Yu, Kezhou; Yang, Meng; Yang, Tianxin; Wang, Rong
Abstract : Nitrooleic acid (OA-NO2 ) is an endogenous lipid product which has novel signaling properties, particularly the activation of peroxisome proliferator-activated receptors. The current study aimed to evaluate the protective effects of OA-NO2 against cisplatin-induced kidney injury in mice. Mice were pretreated with OA-NO2 for 48 h before cisplatin administration, and the cisplatin-caused nephrotoxicity was evaluated. After the cisplatin treatment (72 h), the vehicle-treated mice displayed renal dysfunction, as evidenced by the elevated plasma urea and creatinine, which was consistent with the histological damage, such as tubular necrosis, dilation, protein cast, and desquamation of epithelial cells. In contrast, the severity of the renal dysfunction and histological change were reduced in the OA-NO2 pretreated mice. The renal COX-2 and mPGES-1 mRNAs and their respective proteins expression, together with the renal PGE2 amounts, were induced by the cisplatin treatment, but their initiation was reduced by OA-NO2 . Moreover, the circulating TNF-α, renal TNF-α, IL-1β, MCP-1, ICAM-1, and VACAM-1 mRNA levels were higher in the cisplatin-treated mice, compared with the controls, but they were attenuated in the OA-NO2 pretreatment group. In summary, the pretreatment with OA-NO2 remarkably ameliorated the cisplatin-induced kidney injury in mice, possibly via the inhibition of the inflammatory response, associated with the COX-2/mPGES-1/PGE2 cascade.